Rheological Behavior of Milk From Different Species as a Function of Chemical Composition and Temperature: An Engineering Basis for Milk Processing - Sanches, Halissom Clever [UNESP]; dos Santos, Alexsander Saves [UNESP]; Gonsales, Beatriz Hebeler Pansiera [UNESP]; Borges‐Machado, André Luiz [UNESP]; Ribeiro‐Sanches, Marcio Augusto [UNESP]; Telis‐Romero, Javier [UNESP]; Penna, Ana Lúcia Barretto [UNESP] (Wiley, 2025)
ABSTRACT This study aims to evaluate the rheological behavior of cow, goat, buffalo, and sheep milk over a wide temperature range (1°C–90°C), considering their chemical composition. The milk from the different species showed Newtonian behavior, and the Newton model was the most suitable ( R adj 2 ≥ 0.9979; P (%) ≤ 2.6817; RQME ≤ 0.0333) to predict the rheological behavior of milk over the wide temperature range studied (1°C–90°C). Despite the statistically significant differences in the viscosity of goat and cow milk, the effect size is small in practical terms (on average, less than 4% difference), indicating that the necessary operating conditions are close to those found for a process designed for cow milk. In contrast, buffalo and sheep milk presented, on average, viscosity up to 24%–26% higher than cow and goat milk, which was attributed to the higher content of lipids, ash, and total solids, in addition to structural factors such as fat crystallization, protein interactions, and micellar structure. The Newtonian viscosity of milk from different species decreased with increasing temperature, and the Arrhenius equation described its thermal dependence well. These findings help better understand the rheological properties of milk from different species, supporting the development and improvement of dairy processes and products.